HUBUNGAN ANGKA BEBAS JENTIK (ABJ) DENGAN INSIDENCE RATE DEMAM BERDARAH DENGUE (DBD) DI TINGKAT KABUPATEN SLEMAN TAHUN 2013-2017 - Tri Wahyuni Sukesi; Cincin Tri Astuti (Universitas Ahmad Dahlan, 2020)
Background : Dengue Hemorrhagic Fever (DHF) was widely found in tropical and sub-tropical regions. WHO noted Indonesia as a country with the highest DHF cases in Southeast Asia. DHF was an endemic disease, discovered in1954, entered Indonesia in 1968. In Sleman Regency, the number of DHF cases in2017 was 427 (IR 46.31 of 100,000 population with 3 deaths (CFR 0.7%). The number of cases was decreased, compared to 2016. That was recorded at 880 cases (IR 82.7 of 100,000 population with 9 deaths (CFR 1%). Larva-free number (ABJ) Â in Sleman Regency was 91.79%, below standard 95%. But the incidence of DHF was decreased. The general objective of study was determined the relationship between ABJ with the Incidence Rate of DHF in Sleman Regency in2013-2017.Method : The population was the incidence of DHF in Sleman Regency in 2013 - 2017, using secondary data. The independent variable was ABJ and the Incidence Rate of DHF as the dependent variable. Univariate analysis was done to get a decription of ABJ and IR DHF. Bivariate analysis was performed to examine the relationship between ABJ and DHF Incidence Rate. The strength of relationship was obtained by regression and correlation analysis.Result : these results was showed a very low relationship and a positive pattern. A coefficient of determination was closed to zerro, indicated no relationship.Conclusion : between 2013-2017, the Larva-free Numbers in Sleman Regency was fluctuated, in 2016-2017 it was below standard. Incidence Rate in Sleman Regency 2013-2017 was fluctuated, the lowest case occurred in 2017. There was a weak negative relationship between ABJ and IR DHF in Sleman Regency namely 2013-2017, but statistically not meaningful.